RESEARCH OF QUALITY AND INFLUENCE FACTORS IN BLANKING LAMINATED COPPER SHEET - LIANG Yong; FAN YuJin; ZHENG HaiTao; LI ZheKun; HE Wei; TANG Jun (Jixie qiangdu)
The application of laminated metal sheet in the numerical control busbar blanking process is increasingly wide. In this paper,the blanking process of laminated copper sheet is studied to improve edge quality of parts in blanking laminated metal sheet. Compare single metal sheet blanking process,laminated metal sheet is different. Laminated copper sheet blanking experiments are conducted in the busbar processing machine’s blanking station and taken some approach that through DAQ to collect pressure,displacement sensor test data in blanking laminated copper sheet under different blanking clearance. Blanking force variation trend with displacement is obtained,and relationship between aperture size,deformation collapse height and blanking displacement is also acquired. Data above are analyzed and compared. Studies have shown that blanking force increases with decreasing blanking clearance and deformation collapse height and aperture size accuracy have a lot to do with the layer number of the place of laminated sheet. Compared single metal sheet with laminated metal sheet blanking process,influence factors are more and problems are more complicated which in blanking laminated metal sheet,quality of parts in blanking laminated metal sheet can be improved by controlling some environment which including blanking clearance and blank-holder force.